As dificuldades de aprendizagem dos alunos do 1° ano do ensino fundamental I, relacionadas à leitura e escrita - SOUSA, Antônia Pereira de (2022)
The main objective of this work is to discover the main problems that lead to the learning difficulties in reading and writing, of students of the first year of elementary school I, of the EMEF "Pedro Luiz de Camargo". In order to achieve this objective, a bibliographical research was carried out, which will be presented in the theoretical basis, on the ideas of several authors who approached this thematic, aiming at the understanding of fundamental questions about the Learning and discussing the possible causes that lead to learning difficulties and consequently to school failure. Thus, the theoretical basis of this work is based mainly on the works of authors such as: Azevedo (2014), Bossa (2017), Correia and Martins (1997), Santos and Mendonça (2007) and Soares (2004). Soon after, a field survey was carried out, of a qualitative character, having as an instrument of data collection, an interview with two teachers and with the school counselor, field of research. The results revealed that many students of the first year of the school "Pedro Luiz de Camargo" have learning difficulties, mainly in terms of the acquisition of reading, writing and simple mathematical operations such as adding and diminishing, and that these Difficulties may be related to several factors, such as examples, the absence of family accompaniment, the pedagogical proposal of the school, the lack of teacher training, family problems, the cognitive deficits of the child itself, Among others, and it is of paramount importance to investigate these problems that directly affect the learning of students in order to combat them, aiming at the good performance of the child, before the process teaching-learning.